A new species of Charinus Simon, 1892 (Amblypygi, Charinidae) from termite nests in French Guiana - Réveillion, F.; Maquart, P.o. (Zootaxa, 2015)
The genus Charinus is represented by 51 species, distributed in all tropical regions. Their small size allows them to use a wide range of micro-habitats, from caves, litter to insect nests. The new species C. sillami sp. nov. was found into termite nests of three different species: Neocapritermes taracua, Spinitermes sp. and Embiratermes neotenicus. Only Paracharon caecus (Paleoamblypygi: Paracharontidae) was previously known to be associated with Isoptera. Eleven species of Charinus were previously known from Northern South America. Charinus sillami sp. nov. is the second species of the genus occurring in French Guiana. An updated key of Northern South-American species is provided.